2009
DOI: 10.1303/aez.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of refrigerated non-viable eggs of Riptortus clavatus (Heteroptera: Alydidae) to enhance parasitism by egg parasitoids in soybean field

Abstract: Riptortus clavatus Thunberg (Heteroptera: Alydidae) is an important soybean pest in Korea and Japan. Chemical application is a common control method against R. clavatus although it is not always effective at reducing crop damage. As a biological control, the release of refrigerated stink bug eggs has been suggested because the eggs become non-viable but can still be parasitized by parasitoids. We evaluated the inoculation of refrigerated eggs of R. clavatus as a method to enhance natural parasitism. Overall, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The parasitoid O. nezarae show high dispersal ability (Hirose et al, 1996) and high field parasitism on R. pedestris eggs in Korea (Mainali and Lim, 2012) and Japan (Noda, 1989). While augmentative release of the parasitoid to control R. pedestris can be an alternative control measure, it is not economical (Lim and Mahmoud, 2009) due to both the cost of rearing (Colinet and Boivin, 2011) and the fact that biological control agents have a relatively short life-span, making the production of agents shortly before their intended use important (Colinet and Boivin, 2011). However, producing or obtaining large quantities of suitable hosts right when they are needed is often difficult to achieve (Orr, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parasitoid O. nezarae show high dispersal ability (Hirose et al, 1996) and high field parasitism on R. pedestris eggs in Korea (Mainali and Lim, 2012) and Japan (Noda, 1989). While augmentative release of the parasitoid to control R. pedestris can be an alternative control measure, it is not economical (Lim and Mahmoud, 2009) due to both the cost of rearing (Colinet and Boivin, 2011) and the fact that biological control agents have a relatively short life-span, making the production of agents shortly before their intended use important (Colinet and Boivin, 2011). However, producing or obtaining large quantities of suitable hosts right when they are needed is often difficult to achieve (Orr, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The storage of host eggs in a state suitable for successful development of an endoparasitoid is important both for the mass rearing of natural enemies and to build up the population of natural enemies in the field by mass releasing host eggs when hosts (in the form of natural host eggs) is limiting in the field (Chen and Leopold, 2007). Various studies have found that cold-stored host eggs of various bugs, including R. pedestris could be successfully parasitized by egg parasitoids (Popov, 1974;Corrêa-Ferreira and Moscardi, 1993;Mahmoud and Lim, 2007), and cold-stored host eggs of R. pedestris have been released to increase field parasitism (Lim and Mahmoud, 2009;Alim and Lim, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the release of non-viable, refrigerated eggs in soybean fields as host sources for naturally occurring parasitoids has been suggested as a way to enhance field parasitism by G. japonicum and O. nezarae (Lim and Mahmoud, 2009). As refrigeration renders R. pedestris non-viable, the introduction of such refrigerated eggs may not increase the pest population in the field.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, Lim and Mahmoud (2009) released refrigerated, non-viable eggs of R. pedestris to enhance field parasitism by parasitoids in soybean. The study found higher parasitism on natural eggs of R. pedestris collected in fields, but parasitism by O. nezarae was greatly reduced on released refrigerated eggs.…”
Section: Introductionmentioning
confidence: 99%
“…As both G. japonicum and O. nezarae successfully parasitized R. pedestris eggs that were refrigerated for 30 days in laboratory Lim 2009, 2010), the asymmetrical parasitism by O. nezarae between field-collected natural eggs and released refrigerated eggs was an unexpected outcome. Lim and Mahmoud (2009) suggested that refrigeration of the host eggs may affect interspecific interactions when host eggs are multiparasitized by these two parasitoids.…”
Section: Introductionmentioning
confidence: 99%